Design of flipped classroom lesson in educational electronic environment of maritime higher education institutions - O. Diahyleva; A. Yurzhenko; O. Kononova (Mukachevo State University, 2023)
Online classes (due to COVID, and then because of the war in Ukraine) require the teacher to make constant changes and to use new forms and methods of learning so that students feel free and more independent. Such a learning model as the flipped class is a type of mixed learning, the peculiarity of which is that students work on new educational material at home and consolidate what they have learned in class by performing practical tasks on the topic. The research aims to describe the process of creation and implementation of flipped classroom lessons for ship engineering cadets of a modern maritime higher education institution. The following methods were used in the research: observation, study of practical experience, verification of creative works and application of tests. The example of a flipped classroom lesson on the Learning Management System platform MOODLE is presented in the article. The priority of such lessons is to redesign the learning model so that the cadets are familiar with new material before class. The set of examples of activities that motivate cadets to get ready before class are given. Fourth-year cadets of the ship engineering department of Kherson State Maritime Academy, Ukraine are the main participants of the experiment. The formation of competence regarding Maritime English using a flipped classroom was analysed. The article presents and substantiates the results of the experiment, confirming the positive influence of flipped classrooms on the communicative competence of future ship engineers. It is shown that, using the flipped classroom the teacher gets the opportunity to work with each student individually and immediately focus on the performance of practical tasks; each student can independently, at the necessary pace, review the material, which is available at any time (for those who attended the class, and for those who were absent for some reason). The practical significance of the article is that it demonstrates how the new pedagogical model allows for increased active learning opportunities for cadets of the ship engineering department.